2021
DOI: 10.1111/imj.14814
|View full text |Cite
|
Sign up to set email alerts
|

Febuxostat as a renoprotective agent for treatment of hyperuricaemia: a meta‐analysis of randomised controlled trials

Abstract: Background: The objective of this meta-analysis of randomised controlled clinical trials (RCT) was to evaluate the effects of febuxostat on kidney function in patients with hyperuricaemia.Aims: Febuxostat is a xanthine oxidase inhibitor that decreases uric acid production.Recent studies suggested the renoprotective effect of febuxostat among hyperuricaemia patients. The aim of this study was to evaluate the effects of febuxostat on kidney function in patients with hyperuricaemia.Methods: We conducted electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…Using febuxostat therapy resulted in similar effects on endothelial function in patients on hemodialysis treatment, with a significant drop in SUA levels [68,69]. Recently, a meta-analysis of randomized controlled trials (RCTs) on use of febuxostat carried out by Chewcharat et al reported a reduction in systolic and diastolic blood pressure compared to placebo, apparently with no effect on major CV events, arrhythmias, or stroke events [70]. A systematic review on use of xanthine oxidase inhibitors for prevention of CV events has concluded that they may reduce the incidence of adverse CV outcomes when used in lower doses (<300 mg/day) [71].…”
Section: Hyperuricemia and Cardiovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Using febuxostat therapy resulted in similar effects on endothelial function in patients on hemodialysis treatment, with a significant drop in SUA levels [68,69]. Recently, a meta-analysis of randomized controlled trials (RCTs) on use of febuxostat carried out by Chewcharat et al reported a reduction in systolic and diastolic blood pressure compared to placebo, apparently with no effect on major CV events, arrhythmias, or stroke events [70]. A systematic review on use of xanthine oxidase inhibitors for prevention of CV events has concluded that they may reduce the incidence of adverse CV outcomes when used in lower doses (<300 mg/day) [71].…”
Section: Hyperuricemia and Cardiovascular Diseasementioning
confidence: 99%
“…Recently, Kojima et al reported in the FREED study that febuxostat effectively lowers uric acid to target values and delays the progression of renal dysfunction [88]. The aforementioned meta-analysis by Chewcharat et al reported slowing of renal function decline regardless of baseline function in patients receiving febuxostat compared to placebo [70]. A head to head comparison (allopurinol vs. febuxostat) described higher efficacy of febuxostat to reach target values of SUA than allopurinol in six months and has also shown an increase in eGFR, while they observed a decline of eGFR in the allopurinol group [85].…”
Section: Hyperuricemia and Kidney Diseasementioning
confidence: 99%
“…Systematic reviews examining the effect of urate-lowering therapy (ULT) on kidney function provided contradictory results. 8 18 Systematic reviews reported variable findings: improvement in eGFR report in some 9 , 13 15 , 17 , 18 but not in others; 8 , 11 , 12 improvement in serum creatinine reported in some 8 , 9 , 11 , 14 , 15 , 17 , 18 but not others; 12 , 13 improvement in proteinuria/albuminuria reported in one 16 but not in others; 8 , 9 , 11 , 15 , 18 and reduction in kidney failure risk reported in some 14 , 16 , 18 but not in other systematic reviews. 8 , 15 Two recently published randomized controlled trials (RCTs) showed no significant preservation of kidney function with the use of ULT, 19 , 20 which contradicts findings from the previous RCTs.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in CKD stage 3-4, randomized, placebo-controlled trials have showed either significantly increased eGFR of 3.3 ± 1.2 mL/min/1.73 m 2 due to allopurinol during a 12-month of follow-up 37 or that febuxostat was not significantly associated with eGFR increase (from 31.5 ± 13.6 to 34.7 ± 18.1 mL/ min/1.73 m 2 , P = 0.3) over 6 months of therapy 17 . It is worth noting that a recent meta-analysis of nine randomized placebo-controlled trials (2,141 patients) showed a higher eGFR at 6 months follow-up (weighted mean difference [WMD], 2.69 ml/min/1.73m 2 ; 95%CI, 1.52-3.87) in febuxostat than placebo in patients with CKD (eGFR < 60 ml/min/1.73m 2 ) 38 . www.nature.com/scientificreports www.nature.com/scientificreports/ Head-to-heard comparison of XOIs in the FREED study, the mean change in eGFR from baseline per year revealed no significant differences between febuxostat and allopurinol groups [−0.37 (−2.32 to 1.44) vs. −0.69 (−2.63 to 1.39) mL/min/1.73m 2 , P = 0.606] over 36-month follow-up 22 .…”
Section: Discussionmentioning
confidence: 99%